Analysis of translation of 5’ untranslated regions in colorectal cancer - Silva, Joana (2017)
Carcinogenesis is characterized by a continuous accumulation of genetic alterations that changes the overall gene expression profiles. Those alterations have been stuied by microarray or RNA sequencing that measure the abundance of mRNA but do not provide information on protein synthesis, which is a step closer to end-point of gene expression. Ribosome profiling (Ribo-seq) emerges to monitor in vivo translation by deep sequencing of ribosome-protected mRNA fragments. This technique reveals the presence of ribosomes outside of known protein-coding regions, identifying translation of upstream open reading frames (uORFs) within 5’ untranslated regions (5’UTRs). Our aim is to determine the role of specific uORFs in cancer tumorigenesis, mainly in colorectal cancer (CRC). Thus, we will use already available Ribo-seq data from different cancer cell lines to get the 5’UTR translation profiles to choose potential uORFs-containing targets. Then, we will analyze the role of such uORFs in translational regulation and study the biological function of those translatable uORFs at the level of cell viability and proliferation, and acquisition of malignant features to understand their involvement in CRC development. Based in 5’UTR ribosome occupancy profiles from Ribo-seq analysis we chose ABCE1, PAIP2, eIF4G2 and eIF2A as our uORFs-containing mRNAs. By semi-quantitative RT-PCR ABCE1 transcript is shown down- and up-regulated in HCT116 and SW480 cells, respectively, in comparison to the non-neoplasic colorectal cell line (NCM460). To test the potential function of uORFs of our transcripts, we are now mapping the exact 5’-end of each 5’UTRs by circular rapid amplification of cDNA ends to finally clone them in a reporter plasmid and study their function in translational control.